Surface zooplankton community composition in whale shark (Rhincodon typus) feeding grounds off Sogod Bay, Southern Leyte during August 2013 to March 2014 - Muncada, Paul Matthew L. (Paul Matthew L. Muncada, 2014)
Sampling stations in the study site off Sogod Bay, Southern Leyte were established along the feeding grounds of whale shark (Rhincodon typus). The whale shark season in the area is known to last from November to July. Water samples and physico-chemical parameters from three sampling stations were taken and collected once a month in August and October in year 2013 within the off whale shark season period, and March 2014 within the whale shark season. Abundance, composition, and diversity of zooplankton groups encountered were quantified. Copepods dominated by 66% (Order Calanioda 26%, copepod nauplius 16%, Order Cyclopoida 14% and Order Harpacticoida 10%) of the total zooplankton population. October 2013 had the least mean density of 1.9x10 raised to the power of 3 ind./L. August 2014 samples had the least zooplankton diversity of H'= 1.58. Samples obtained during the whale shark season, March 2014, showed the highest total zooplankton abundance at 7.7x10 raised to the power of 3 ind./L. This also yielded the highest zooplankton community diversity of H'= 2.53.